2022
DOI: 10.1007/s00240-022-01357-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phytate on hypercalciuria secondary to bone resorption in patients with urinary stones: pilot study

Abstract: The objective is to evaluate the effect of phytate supplements on calciuria in patients with urinary stones and elevated bone resorption. The secondary objective is to analyze the therapeutic effect of phytate based on measurements of serum markers of bone resorption. This is a controlled randomized study included patients according to predefined inclusion and exclusion criteria, and randomized them into two groups. Patients in the phytate group received a 380 mg capsule of calcium-magnesium InsP6 (Salvat Labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For example, previous research reported that InsPs can inhibit osteoclastogenesis and mineralization of osteoblasts [33]. Another recent study showed that the intake of InsP6 by menopausal women with hypercalciuria significantly decreased the elimination of urinary calcium [34]. In these cases, phytate or its derivatives do not act as crystallization inhibitors, but due to their activity at the cellular level, the elimination of urinary calcium decreases, so the supersaturation of calcium salts also decreases, and as a consequence their ability to crystallize.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous research reported that InsPs can inhibit osteoclastogenesis and mineralization of osteoblasts [33]. Another recent study showed that the intake of InsP6 by menopausal women with hypercalciuria significantly decreased the elimination of urinary calcium [34]. In these cases, phytate or its derivatives do not act as crystallization inhibitors, but due to their activity at the cellular level, the elimination of urinary calcium decreases, so the supersaturation of calcium salts also decreases, and as a consequence their ability to crystallize.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Additionally, we added phytate owing to its capacity to inhibit calcium phosphate lithiasis growth and to decrease bone resorption. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although the mechanisms involved in bone metabolism differ from those of kidney stone formation, some similarity exists, especially with regard to the inorganic ions that are involved in the process. IP6 was shown to reduce calciuria in patients with hypercalciuria because of increased bone resorption, resulting in a reduced tendency for kidney stone formation in these patients [ 171 ]. The beneficial effects of IP6 with regards to bone health may be attributable to the protective role in bone decalcification by combining with hydroxyapatite, thereby reducing the rates of its dissolution [ 64 ] ( Table 1 ).…”
Section: Ip6 and Bone Healthmentioning
confidence: 99%